Reduction of nitrate to nitrite in water by acid-washed zero-valent zinc. Issue 4 (3rd March 2020) - Chiu, Yi-Ting; Lin, Chu-Hong; Lee, Jechan; Lin, Kun-Yi Andrew
ABSTRACT: This study examines capability of zero-valent zinc (ZVZ), prepared from acid-washing zinc powder, for reducing nitrate to nitrite under various conditions. While higher dosages of ZVZ and elevated temperatures enhance nitrate reduction, effect of pH is validated as the most important factor to nitrate reduction as the nitrate reduction efficiency and kinetics are significantly enhanced under acidic conditions. However, nitrate reduction by ZVZ is inhibited under alkaline conditions. ZVZ also remains effective for nitrate reduction in the presence of other anions. The findings gained in this study are critical to design and operate nitrate reduction using zero-valent metals.